Global perspectives on rights of nature Subsidiarity as a guiding compass - Tahyné Kovács Ágnes (XXII International Scientific Conference "Legal Days – Prof. Slavko Caric Law and justice" : Law and Justice, 2025)
Amid the escalating triple planetary crisis—climate change, biodiversity loss, and pollution—legal cultures worldwide reflect evolving human-nature relationships. This paper examines the Rights of Nature as an emerging legal paradigm, analyzing key global case studies through the lens of subsidiarity. It situates the Rights of Nature within broader environmental regulatory frameworks and traces its development across legislative levels, from national constitutions to local ordinances. Through these examples, the paper illustrates how subsidiarity shapes the application of this concept, balancing local autonomy with higher-level governance. Additionally, it evaluates landmark court cases that invoke Rights of Nature in their rulings or reasoning, highlighting their legal significance. The paper also explores the concept's nascent emergence in Europe, identifying early trends and potential implications. By mapping these cases, the analysis identifies shared characteristics, underscores distinctions, and evaluates subsidiarity's role in shaping effective environmental governance.